eHealth literacy and socioeconomic and demographic characteristics of parents of children needing paediatric surgery in Sweden - Ólöf Kristjánsdóttir; Anna Welander Tärneberg; Pernilla Stenström; Charlotte Castor; Inger Kristensson Hallström (Wiley, 2023)
Abstract Aim The aim of the study was to describe different eHealth literacy domains among parents of children needing paediatric surgery in Sweden, and the correlation between these eHealth literacy domains and parents' socioeconomic factors and demographic characteristics. Design Descriptive correlational design. Method Thirty‐five Swedish‐speaking parents participated as a historical control group within an ongoing Swedish clinical trial developing eHealth solutions for families after hospital care; of these, 30 completed the eHealth Literacy Questionnaire and the socioeconomic and demographic questionnaire. Results Of the seven eHealth literacy domains assessed, parents' strengths lay in those pertaining to their own digital competence, control and safety, while their weakness concerned their motivation to engage with digital services, and their ability to access eHealth platforms that work. Overall, parents presented adequate eHealth literacy. Of the five socioeconomic and demographic variables assessed (i.e. monthly wages, education levels, age, gender and residency), monthly wages correlated the strongest, and positively, with the seven eHealth literacy domains.